Intronic SNP in ESR1 encoding human estrogen receptor alpha is associated with brain ESR1 mRNA isoform expression and behavioral traits. - Julia K Pinsonneault; John T Frater; Benjamin Kompa; Roshan Mascarenhas; Danxin Wang; Wolfgang Sadee (PLoS ONE)
Genetic variants of ESR1 have been implicated in multiple diseases, including behavioral disorders, but causative variants remain uncertain. We have searched for regulatory variants affecting ESR1 expression in human brain, measuring allelic ESR1 mRNA expression in human brain tissues with marker SNPs in exon4 representing ESR1-008 (or ESRα-36), and in the 3'UTR of ESR1-203, two main ESR1 isoforms in brain. In prefrontal cortex from subjects with bipolar disorder, schizophrenia, and controls (n = 35 each; Stanley Foundation brain bank), allelic ESR1 mRNA ratios deviated from unity up to tenfold at the exon4 marker SNP, with large allelic ratios observed primarily in bipolar and schizophrenic subjects. SNP scanning and targeted sequencing identified rs2144025, associated with large allelic mRNA ratios (p = 1.6E10-6). Moreover, rs2144025 was significantly associated with ESR1 mRNA levels in the Brain eQTL Almanac and in brain regions in the Genotype-Tissue Expression project. In four GWAS cohorts, rs2104425 was significantly associated with behavioral traits, including: hypomanic episodes in female bipolar disorder subjects (GAIN bipolar disorder study; p = 0.0004), comorbid psychological symptoms in both males and females with attention deficit hyperactivity disorder (GAIN ADHD, p = 0.00002), psychological diagnoses in female children (eMERGE study of childhood health, subject age ≥9, p = 0.0009), and traits in schizophrenia (e.g., grandiose delusions, GAIN schizophrenia, p = 0.0004). The first common ESR1 variant (MAF 12-33% across races) linked to regulatory functions, rs2144025 appears conditionally to affect ESR1 mRNA expression in the brain and modulate traits in behavioral disorders.